Tantangan Penerapan Pajak Karbon Di Indonesia Upaya Mengatasi Dampak Perubahan Iklim Dan Mendukung Pembangunan Ekonomi Berkelanjutan - Indah Tri Sari Harahap; Keisya Putri Balqis; Zulfahri Salim; Dini Vientiany (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this research is to find out how the challenges of carbon tax implementation in indonesia against the impact of climate change and supporting sustainable economic development, carbon tax is a tax imposed on the massive release of emissions through the burning of carbon-based fossil fuels. In conducting this research, the method used is library research, which involves in-depth analysis and evaluation of various relevant literature sources. This research provides an in-depth understanding of these complexities and their influence on sustainable economic development in Indonesia. The level of effectiveness of cooperation between government, industry and society in formulating a sustainable carbon tax policy in Indonesia is an important aspect in the discussion of the successful implementation of the policy. Close collaboration between the three entities will play a crucial role in ensuring that the carbon tax policy is well implemented and positively impacts Indonesia's sustainable economic development efforts.